Peculiarities of using imported and homemade machinery in modern ukrainian agriculture - Demianenko, I. (ТДАТУ, 2018)
EN: The article concerns peculiarities, perspectives, and problems of using agricultural machinery in Ukraine. The facts and figures of operating new and earlier used foreign machines, the lack of new up-to-date machinery of domestic manufacturers are analyzed and described. UK: Увагу статті зосереджено UA особливих умовах, цифрах та фактах щодо використання імпортної та вітчизняної техніки в агросекторі України.
Keywords: агросектор України; using agricultural machinery; machinery